2016
DOI: 10.1186/s40064-016-3359-y
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates therapy for osteoarthritis: a meta-analysis of randomized controlled trials

Abstract: High-turnover type bone metabolism derangement has been considered to be one of the major causes of osteoarthritis (OA). Bisphosphonates can attach to hydroxyapatite binding sites on bony surfaces, particularly those which are undergoing active bone resorption. To evaluate the effectiveness of bisphosphonates in OA treatment, literature databases were searched from inception to February 28, 2016 for clinical studies of bisphosphonates for OA treatment. All randomized controlled trials in which bisphosphonates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 29 publications
1
30
1
Order By: Relevance
“…In addition to the biphasic nature of bone remodeling in OA, the rates of bone remodeling even at the early OA stages may differ between individuals; a novel diagnostic approach may be required to assess those rates and predict whether a patient would be a good candidate for the treatment with antiresorptive agents 55 . Our efficacy results disagree with prior meta-analyses, which presented positive conclusions about the effectiveness of bisphosphonates in OA 37,38 . The first publication, by Davis et al, 2013 reviewed both RCTs and observational studies performed in the knee, hip or spine OA patients but used only three RCTs in its meta-analyses (Spector 2005 and North American and European cohorts from Bingham et al, 2006, all studying oral risedronate in knee OA) 37 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition to the biphasic nature of bone remodeling in OA, the rates of bone remodeling even at the early OA stages may differ between individuals; a novel diagnostic approach may be required to assess those rates and predict whether a patient would be a good candidate for the treatment with antiresorptive agents 55 . Our efficacy results disagree with prior meta-analyses, which presented positive conclusions about the effectiveness of bisphosphonates in OA 37,38 . The first publication, by Davis et al, 2013 reviewed both RCTs and observational studies performed in the knee, hip or spine OA patients but used only three RCTs in its meta-analyses (Spector 2005 and North American and European cohorts from Bingham et al, 2006, all studying oral risedronate in knee OA) 37 .…”
Section: Discussioncontrasting
confidence: 99%
“…The second, most recent meta-analysis on the topic, by Xing et al, 2016 also arrived at a positive verdict on the efficacy of bisphosphonates in OA 38 . However, this study had major methodological flaws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a one-year, placebo-controlled trial that included 59 patients with knee OA treated with zoledronic acid 5 mg intravenously as a single infusion, a significant reduction in visual analogue pain scores versus placebo was seen after six months, but not after 12 months; interestingly, a significant reduction in bone marrow lesions was detected with magnetic resonance imaging (MRI) [ 108 ]. In a recent meta-analysis of randomised controlled trials that compared bisphosphonate therapy with placebo or conventional medication, Xing et al assessed the efficacy of bisphosphonates in OA; 15 studies were eligible for analysis and they included 3566 participants (1517 on bisphosphonates) [ 109 ]. It was shown that bisphosphonate therapy leads to significant improvements in pain, stiffness and function in OA patients assessed using the WOMAC score.…”
Section: Novel Therapeutics Based On the Molecular Pathogenesis Ofmentioning
confidence: 99%
“…Blocking bone remodelling with a bisphosphonate early in murine osteoarthritis development appears to block pain without affecting structural disease, according well with clinical studies in osteoarthritis in which bisphosphonates are not disease-modifying when given in established disease. 156 , 157 …”
Section: Discussionmentioning
confidence: 99%